2022
DOI: 10.1007/s00405-022-07384-w
|View full text |Cite
|
Sign up to set email alerts
|

The bone conduction implant BONEBRIDGE increases quality of life and social life satisfaction

Abstract: Purpose Transcutaneous active bone conduction hearing aids represent an alternative approach to middle ear surgery and conventional hearing aids for patients with conductive or mixed hearing loss. The aim of this study was to determine quality of life, subjective hearing experience and patients’ satisfaction after implantation of a bone conduction hearing aid. Methods This monocentric and retrospective study included twelve adult patients who received a bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
(40 reference statements)
1
1
0
Order By: Relevance
“…It follows that, due to the huge improvement of speech intelligibility through the use of a BCI in patients with bilateral conductive hearing impairment, the mean level of satisfaction may result in an overestimation of the subjective benefits of patients affected by unilateral conductive hearing loss fitted with monaural Bonebridge. According to a recent work by Irmer et al who highlighted the benefits of BC implantation in terms of subjective hearing 26 , our results account for the better speech perception of patients implanted with monaural Bonebridge.…”
Section: Discussionsupporting
confidence: 71%
“…It follows that, due to the huge improvement of speech intelligibility through the use of a BCI in patients with bilateral conductive hearing impairment, the mean level of satisfaction may result in an overestimation of the subjective benefits of patients affected by unilateral conductive hearing loss fitted with monaural Bonebridge. According to a recent work by Irmer et al who highlighted the benefits of BC implantation in terms of subjective hearing 26 , our results account for the better speech perception of patients implanted with monaural Bonebridge.…”
Section: Discussionsupporting
confidence: 71%
“…Full text review of these 290 articles was conducted, and a total of 52 articles were selected for inclusion (Fig. 1) (13–64). Critical appraisal of studies indicated an acceptably low risk of bias for the majority of included studies (Fig.…”
Section: Resultsmentioning
confidence: 99%